2018
DOI: 10.5194/nhess-18-1133-2018
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for land degradation and desertification assessment using geospatial techniques

Abstract: Abstract. Land degradation reduces the production of biomass and vegetation cover for all forms of land use. The lack of specific data related to degradation is a severe limitation for its monitoring. Assessment of the current state of land degradation or desertification is very difficult because this phenomenon includes several complex processes. For that reason, no common agreement has been achieved among the scientific community for its assessment. This study was carried out as an attempt to develop a new a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Recent studies have also shown that with the help of the integrated use of GIS and RS analyses of both temporal and spatial dynamics of land-cover changes caused by drying surface water bodies become possible, [46] analyzing potential changes occurring among land cover features and develop the baseline maps of desertification or land-cover [6,16,44]. Concerning these studies, RS implies either satellite images or aerial photography to perform a trend analysis for future scenarios and create trend maps showing the possible changes in land cover condition over a certain period [27].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also shown that with the help of the integrated use of GIS and RS analyses of both temporal and spatial dynamics of land-cover changes caused by drying surface water bodies become possible, [46] analyzing potential changes occurring among land cover features and develop the baseline maps of desertification or land-cover [6,16,44]. Concerning these studies, RS implies either satellite images or aerial photography to perform a trend analysis for future scenarios and create trend maps showing the possible changes in land cover condition over a certain period [27].…”
Section: Methodsmentioning
confidence: 99%
“…LD has been defined as … any decrease in the land potential through one or combination of several processes, including water erosion, wind, and vegetation degradation, which are affected by potential human and natural factors (Prăvălie, Savulescu, Patrich, Dumitrascu, & Bandoc, 2017; UNEP, 1994). LD not only has more prevalence in arid and semiarid areas (Masoudi, Jokar, & Pradhan, 2018) but also has many undesirable effects on healthy adjacent areas, especially in the developing countries (Hazbavi, Kalehhouei, & Khalili Moghadam, 2020; Hazbavi, Sadeghi, Gholamalifard, & Davudirad, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the world about 6 million ha of agriculture land becomes unproductive due to soil degradation processes (Asio et al, 2009). Land degradation decreases land capability and causes deterioration in soil productivity (FAO/UNEP, 1978;Berry, 2003;Bai et al, 2008;Pierre, 2010;El Baroudy, 2011;Gessesew, 2017 andMasoudi et al, 2018). Eswaran et al (2001) stated that about 1360 million ha of land on the worldwide are moderately to severely degrade.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of soil degradation on ecological function ultimately affect on quality of life (El Baroudy, 2011;Masoudi, 2014;Vu et al, 2014;El-Baroudy, 2015;Masoudi and Amiri, 2015;Rashed, 2016 andSadeghi et al 2017). Land degradation assessment is difficult because it includes several complex processes (Safriel, 2007;Bai etal., 2008;Jankava et al, 2017 andMasoudi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%